Individualni pouk in načini poučevanja učiteljev flavte na posameznih učnih stopnjah v glasbeni šoli - Kavčič Pucihar, Ana; Rotar Pance, Branka (Revija za elementarno izobraževanje, 2017)
Flute Teachers’ One-to-One Instructional Strategies at Individual Teaching Stages in Music School. This article focuses on one-to-one studio based instrumental instruction in music schools. Some novelties in the music school woodwind curricula are presented within various contexts. Teacher – student relationship, their interactions, and knowledge transfer are essential in individual instrumental instruction. The learning process is systematically structured within six teaching stages, ranging from new content presentation to learning reviews. We examined music school flute teachers’ beliefs (N=78) about teaching stages in individual studio based instruction. We researched their new content teaching strategies, guided practice and reinforcement, feedback, homework monitoring strategies, formative review and assessment within music studio academic year.